Evaluating Intraplant Cotton Fiber Variability. Issue 2 (1st March 2015) - Kothari, Neha; Dever, Jane; Hague, Steve; Hequet, Eric
ABSTRACT: It is well documented that cotton fiber variability exists across and within cultivars, across environments, soil quality, biotic and abiotic stresses. Having uniform fiber quality is a primary goal for cotton breeders to enhance profitability and sustainability. The objective of this research was to identify the within‐plant variability in fiber quality of six diverse genotypes of Gossypium hirsutum and Gossypium barbasense . This research was conducted in College Station, TX, for 3 yr in 2009, 2010, and 2011 at the Texas A&M AgriLife Research farm. Fiber samples were collected from individual sympodial branches of the plants in three replications and ginned on a tabletop saw gin. Fiber‐quality testing was done using the Advanced Fiber Information System. Statistical analyses inclusive of ANOVA and best linear unbiased predictors and fiber correlations were performed. A distinct pattern of within‐plant fiber variability was observed, with a trend showing that beneficial traits lie in the bottom sympodial fruiting positions while the poor‐quality bolls are located at the higher sympodial positions within the plant. This pattern was seen across all genotypes in all years. Percentage of difference in fiber length among the longest and shortest fibers within the plant showed that 'FM 832' had the maximal within‐plant fiber length variability while 'DP HTO Pima' had the least within‐plant length variability. Correlation analyses revealed a strong negative relationship between fiber length and standard fineness and a positive relationship between length and fiber maturity. A positive correlation was observed between short fiber content, immature fiber content and fiber neps.